Analytic next-to-leading order Yukawa and Higgs boson self-coupling corrections to gg → HH at high energies - Joshua Davies; Kay Schönwald; Matthias Steinhauser; Hantian Zhang (Journal of High Energy Physics)
Abstract We consider electroweak corrections to Higgs boson pair production, taking into account the top quark Yukawa and Higgs boson self couplings. Using differential equations we compute a deep expansion of all master integrals in the high-energy limit and present analytic results for the two-loop box-type form factors. We show that precise numerical results can be obtained even for relatively small values of the Higgs boson transverse momentum. We compare against recent numerical results and find good agreement.